Physiological regulation of calcium and phosphorus utilization in laying hens - Sinclair-Black, Micaela; Garcia, R. Alejandra; Ellestad, Laura E. (Frontiers in Physiology, 2023)
Commercial laying hens can produce one egg approximately every 24 hours. During this process, regulatory systems that control vitamin D3 metabolism, calcium and phosphorus homeostasis, and intestinal uptake of these minerals work in concert to deliver components required for eggshell calcification and bone mineralization. Commercial production cycles have been extended in recent years to last through 100 weeks of age, and older hens often exhibit an increased prevalence of skeletal fractures and poor eggshell quality. Issues such as these arise, in part, through imbalances that occur in calcium and phosphorus utilization as hens age. As a result, an in-depth understanding of the mechanisms that drive calcium and phosphorus uptake and utilization is required to develop solutions to these welfare and economic challenges. This paper reviews factors that influence calcium and phosphorus homeostasis in laying hens, including eggshell formation and development and roles of cortical and medullary bone. Metabolism and actions of vitamin D3 and physiological regulation of calcium and phosphorus homeostasis in key tissues are also discussed. Areas that require further research in avian species, such as the role of fibroblast growth factor 23 in these processes and the metabolism and action of bioactive vitamin D3, are highlighted and the importance of using emerging technologies and establishing in vitro systems to perform functional and mechanistic studies is emphasized.